Effects of conservation strip and crop type on natural enemies of Delia radicum. (14th August 2015) - Nilsson, U.; Rännbäck, L.‐M.; Anderson, P.; Björkman, M.; Futter, M.; Rämert, B.
Abstract: This 3‐year field study investigated the combined effect of floral resources and perennial shelter habitats (i.e. conservation strips), and crop rotation in supporting natural enemies of the cabbages root fly, Delia radicum . Habitat manipulation with conservation strips increased the overall catches of hymenopteran parasitoids. However, conservation strips did not increase parasitism by either of the two dominant parasitoid species, Trybliographa rapae and Aleochara bipustulata, in any study year. In fact, higher parasitism was found in control plots in the second year. This could be explained by parasitoid mobility and higher patch detectability, as more plants in the control plots were infested with D. radicum larvae. Conservation strips did not result in increased predation of D. radicum eggs. However, the activity densities of two Bembidion species were correlated with egg predation. The species assemblage distribution of epigeal predators was best explained by seasonal period, followed by year and, to a low extent, crop type, while treatment with conservation strips had no effect. However, during the egg laying peak of D. radicum, a higher number of A. bipustulata, an important larval predator was observed in conservation strips during one study year. In conclusion, positive effects of conservation strips were demonstrated for abundance of some natural enemies of D. radicum, but a consistent increase in performance could not be adequately demonstrated due to experimental set‐up, the short timescale and the complex landscape in which our study site was located.